Occupancy of yellow‐billed and Pacific loons: evidence for interspecific competition and habitat mediated co‐occurrence. (18th March 2014) - Haynes, Trevor B.; Schmutz, Joel A.; Lindberg, Mark S.; Wright, Kenneth G.; Uher‐Koch, Brian D.; Rosenberger, Amanda E.
<x xml:space="preserve">Abstract</x> Interspecific competition is an important process structuring ecological communities, however, it is difficult to observe in nature. We used an occupancy modelling approach to evaluate evidence of competition between yellow‐billed (Gavia adamsii) and Pacific (G. pacifica) loons for nesting lakes on the Arctic Coastal Plain of Alaska. With multiple years of data and survey platforms, we estimated dynamic occupancy states (e.g. rates of colonization or extinction from individual lakes) and controlled for detection differences among aircraft platforms and ground survey crews. Results indicated that yellow‐billed loons were strong competitors and negatively influenced the occupancy of Pacific loons by excluding them from potential breeding lakes. Pacific loon occupancy was conditional on the presence of yellow‐billed loons, with Pacific loons having almost a tenfold decrease in occupancy probability when yellow‐billed loons were present and a threefold decrease in colonization probability when yellow‐billed loons were present in the current or previous year. Yellow‐billed and Pacific loons co‐occurred less than expected by chance except on very large lakes or lakes with convoluted shorelines; variables which may decrease the cost of maintaining a territory in the presence of the other species. These results imply the existence of interspecific competition between yellow‐billed and Pacific loons for nesting lakes; however, habitat characteristics which facilitate visual and spatial separation of territories can reduce competitive interactions and promote species co‐occurrence.